Economic Analysis of Added Value and Marketing of Hi-Pro-Ca Amplang Crackers Made from Snakehead Fish (Channa striata) in Teluk Empening Village - Fathan Nabiil Nandana Dhitama; Junianto Junianto (Jurnal Sains dan Teknologi Perikanan, 2026)
This study aims to analyze the added value and marketing system of processed snakehead fish products into amplang crackers in Teluk Empening Village, Terentang District, Kubu Raya Regency, West Kalimantan Province. This study uses a survey method, in which respondents are determined using purposive sampling. This study was conducted in November 2025. The results of the study identified one processed snakehead fish (Channa striata) product, namely Hi-Pro-Ca Amplang Crackers. Based on Hayami's value-added analysis, the cost of raw materials for production is IDR 25.000/kg. This processing generates added value of IDR 141.000/kg. With a value-added ratio of 29,38%, this indicates the financial feasibility of the business. The distribution of returns from the processing of Hi-Pro-Ca Amplang Crackers shows that the largest proportion is allocated to other input contributions at 68,90%, followed by entrepreneur profits at 27,80%, and the remainder as labor income at 3,30%. The high share of other input contributions is due to the intensive use of supporting materials. The marketing system for this product is carried out directly and marketed through several business partners.